Occupational stress, anxiety and coping strategies in police officers - Daniela Acquadro Maran; Antonella Varetto; Massimo Zedda; Valentina Ieraci (2015)
Studies on occupational stress have shown that police officers are exposed to stressful events more often than other workers and this can result in impaired psychosocial well-being and physical health.To measure the level of stress experienced, the consequences in terms of anxiety and the coping strategies adopted in a sample of police officers working in a large city in northern Italy.We used the Police Stress Questionnaire and the Distress Thermometer to measure occupational stress, the State-Trait Anxiety Inventory to measure anxiety and the Brief COPE questionnaire to measure coping strategies.Six hundred seventeen police officers completed the questionnaire, a response rate of 34%. Differences between genders, sectors and roles emerged, but overall the study population generally demonstrated good use of positive coping strategies. Women in all operational service roles were more vulnerable to both organizational and operational stressors than men (P < 0.001), while in the interior department, men were more vulnerable to organizational stressors (P < 0.05).Our results suggest that for Italian police officers, training courses and support in dealing with occupational stress should take into account gender, role and type of work. Tailored training courses and support programmes could be useful and effective tools for preventing stress before it becomes chronic.